2014
DOI: 10.4330/wjc.v6.i6.353
|View full text |Cite
|
Sign up to set email alerts
|

Essential hypertension and oxidative stress: New insights

Abstract: Essential hypertension is a highly prevalent pathological condition that is considered as one of the most relevant cardiovascular risk factors and is an important cause of morbidity and mortality around the world. Despite the fact that mechanisms underlying hypertension are not yet fully elucidated, a large amount of evidence shows that oxidative stress plays a central role in its pathophysiology. Oxidative stress can be defined as an imbalance between oxidant agents, such as superoxide anion, and antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 145 publications
1
124
0
6
Order By: Relevance
“…Hypertension is associated with cardiovascular fibrosis, remodeling and endothelial dysfunction, alterations where oxidative stress plays a key role [37][38][39]. Similar cardiovascular alterations have been found in adult IUGR rats [40][41][42] and therefore oxidative stress has been proposed as a possible mechanism implicated in fetal programming of hypertension [7,43].…”
Section: Discussionmentioning
confidence: 69%
“…Hypertension is associated with cardiovascular fibrosis, remodeling and endothelial dysfunction, alterations where oxidative stress plays a key role [37][38][39]. Similar cardiovascular alterations have been found in adult IUGR rats [40][41][42] and therefore oxidative stress has been proposed as a possible mechanism implicated in fetal programming of hypertension [7,43].…”
Section: Discussionmentioning
confidence: 69%
“…While the biological mechanism underlying a positive association between selenium and blood pressure measure is not yet fully understood, selenium's effect on oxidative stress has been investigated in animal studies. As a key component of many antioxidant enzymes, such as glutathione peroxidase (GPx) selenium plays an important role in oxidative stress [27], which is recognized as one of the fundamental mechanisms underlying hypertension [2]. An experimental study had observed that selenium at low doses can provide significant protection of the human coronary artery endothelium against damage by oxidative stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that oxidative stress is one of the fundamental mechanisms underlying hypertension [2]. Antioxidants inhibit oxidation reactions, thereby reducing the number of free radicals produced and the amount of damage they can cause.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 In addition, population-based observational studies demonstrated an inverse correlation between plasma antioxidant levels and blood pressure levels. 32 An increased local ROS concentration in the kidney may have a pivotal role in the generation of hypertension. ROS-induced vascular remodeling impairs autoregulation and may lead to distal tubulointerstitial ischemia.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 99%